Characterization of Summertime Aerosol Particles Collected at Subway Stations in Seoul, Korea Using Low-Z Particle Electron Probe X-ray Microanalysis - BoWha Kim; Hae-Jin Jung; Young-Chul Song; Mi-Jung Lee; HyeKyeong Kim; Jo-Chun Kim; Jongryeul Sohn; Chul-Un Ro (Asian Journal of Atmospheric Environment, 2010)
A quantitative single particle analytical technique, denoted low-Z particle electron probe X-ray microanalysis (low-Z particle EPMA), was applied to characterize particulate matters collected at two underground subway stations, Jegidong and Yangje stations, in Seoul, Korea. To clearly identify the source of the indoor aerosols in the subway stations, four sets of samples were collected at four different locations within the subway stations: in the tunnel; at the platform; near the ticket office; nearby outdoors. Aerosol samples collected on stages 2 and 3 (Dp: 10-2.5 μm and 2.5-1.0 μm, respectively) in a 3-stage Dekati PM10 impactor were investigated. Samples were collected during summertime in 2009. The major chemical species observed in the subway particle samples were Fe-containing, carbonaceous, and soil-derived particles, and secondary aerosols such as nitrates and sulfates. Among them, Fe-containing particles were the most popular. The tunnel samples contained 85-88% of Fe-containing particles, with the abundance of Fe-containing particles decreasing as the distances of sampling locations from the tunnel increased. The Fe-containing subway particles were generated mainly from mechanical wear and friction processes at rail-wheel-brake interfaces. Carbonaceous, soil-derived, and secondary nitrate and/or sulfate particles observed in the underground subway particles likely flowed in from the outdoor environment by human activities and the air-exchange between the subway system and the outdoors. In addition, since the platform screen doors (PSDs) limit air-mixing between the tunnel and the platform, samples collected at the platform at the Yangjae station (with PSDs) showed a marked decrease in the relative abundances of Fe-containing particles compared to the Jegidong station (without PSDs).